Evaluation of mandibular canal and anatomical variations with mangetic resonance imaging method retrospectively - BORAHAN, MEHMET OĞUZ; ÇİMŞİT, NURİ ÇAGATAY (My University, 2022)
AIM: Mandibular canal (MC) contains vascular bundle and inferior alveolar nerve (IAN). The entrance of mandibular canal to the mandible is mandibular foramen and MC reaches mental foramen at the anterior region of mandible. The course of MC itself is variable. While studies with two-dimensional radiographies revealed frequency of MC variation is around % 0.08- 16.8, studies with three-dimensional imaging methods revealed a higher range which is % 9.8 – 65. Evaluating MC variations with soft tissue imaging methods demonstrated even higher ranges in previous studies. In this study, anatomical variations of MC were observed with magnetic resonance imaging (MRI) method. MATERIAL AND METHOD: A total of 2328 patients MRI between 2013-2018 from the archive of Marmara University Hospital, Department of Radiology were examined retrospectively. After the application of exclusion criterias, 220 MRI images (440 as total, left and right) were evaluated in T1-weighted, T2-weighted and Proton Density images of spin echo and turbo sequences. RESULTS: Examination of the images revealed 66.4% of MC were not bifid. Forward canals in 12.5% (with confluence) and 1.4% (without confluence), retromolar canals in 7.3%, buccolingual canals in 0.9% (0.7% lingual, 0.2% buccal) and dental canals in 7.3% were detected. Morphology of IAN was also classified in our study and found as Type 1 (75.2%), Type 2 (21.8%) and Type 3 (3%). CONCLUSION: MRI is a soft tissue imaging method of head and neck region which is non-invasive and does’nt contain radiation. MRI can be used for detecting MC and its anatomical variations as well as cone beam computed tomography (CBCT) which is also a popular imaging method in dentistry. MC may not be visible on CBCT images due to the trabeculation of bone density. Benefit of using MRI for examination of MC is to be able to observe the soft tissue component of the structure.
Keywords: Anatomical variation; Bifid mandibular canal; Cone beam computed tomography; Mandibular canal; Magnetic resonance imaging